The SPIRIT Action Framework: A structured approach to selecting and testing strategies to increase the use of research in policy. (July 2015) - Redman, Sally; Turner, Tari; Davies, Huw; Williamson, Anna; Haynes, Abby; Brennan, Sue; Milat, Andrew; O'Connor, Denise; Blyth, Fiona; Jorm, Louisa; Green, Sally
Abstract: The recent proliferation of strategies designed to increase the use of research in health policy (knowledge exchange) demands better application of contemporary conceptual understandings of how research shapes policy. Predictive models, or action frameworks, are needed to organise existing knowledge and enable a more systematic approach to the selection and testing of intervention strategies. Useful action frameworks need to meet four criteria: have a clearly articulated purpose; be informed by existing knowledge; provide an organising structure to build new knowledge; and be capable of guiding the development and testing of interventions. This paper describes the development of the SPIRIT Action Framework. A literature search and interviews with policy makers identified modifiable factors likely to influence the use of research in policy. An iterative process was used to combine these factors into a pragmatic tool which meets the four criteria. The SPIRIT Action Framework can guide conceptually-informed practical decisions in the selection and testing of interventions to increase the use of research in policy. The SPIRIT Action Framework hypothesises that a catalyst is required for the use of research, the response to which is determined by the capacity of the organisation to engage with research. Where there is sufficient capacity, a series of research engagement actions might occur that facilitate research use . These hypotheses are being tested in ongoing empirical work. Highlights: There is a lack of action-oriented approaches to guide use of research in policy. Our framework provides a pragmatic basis to develop and test interventions. It can identify the intervention strategies that are most likely to be effective. It has the potential to guide knowledge development and practical decisions. The framework draws on and extends recent theories on knowledge exchange.